Visual training: neuro-visual enhancement in athletes - Tranchita, E.; Segnalini, A.; Licoccia, G.; Sferra, Y.; Marchegiani, C. (Medicina dello Sport, 2017)
BACKGROUND: Sport-Vision is a new method which helps enhancing visual abilities in athletes who practice any kind of sport, especially in disciplines in which ball speed is crucial. METHODS: In this study were used biofeedback instruments, based on cortical answers (CRT), able to stimulate optical fibers and occipital cerebral cortex. Visual evoked potentials (VEP) were measured to evaluate improvements in retino-cortex conduction time. RESULTS: After 10 training sessions 18 athletes on a total of 20, showed objective and subjective improvements in overall visual ability. CONCLUSIONS: This method is able to enhance athletes visual ability, reaching a condition of ipervision and reducing retino-cortex conduction time that could lead to an improvement in sport performance of athletes.